PENGELOLAAN PERPUSTAKAAN YANG BAIK MENDUKUNG PROSES PEMBELAJARAN YANG EFEKTIF DAN EFISIEN - Bajongga Silaban; Januaris Pane (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
The library is the heart of a school which has a very vital function in supporting the learning process. Therefore, the school library with the ranks of librarians in it, has an obligation to "turn on" the library either through the services provided to visitors, or through other activities carried out inside or outside the library. Through the Institute of Research and Community Service of Nommensen HKBP University, several lecturers carried out community service activities to Senior High School Nasrani 1 Medan carrying out workshops in terms of fostering library management according to the demands and needs of the school . This activity is very important and meaningful, because it can help and better understand in managing in the field of collection procurement, collection inventory, collection classification, and main cataloging. Through this workshop, the librarian will further broaden his knowledge in carrying out his duties in serving students, teachers and other visitors who are registered and not in the library